Ideal step size estimation for the multinomial logistic regression - Ramirez Orihuela, Gabriel (2024)
At the core of deep learning optimization problems reside algorithms such as the Stochastic Gradient Descent (SGD), which employs a subset of the data per iteration to estimate the gradient in order to minimize a cost function. Adaptive algorithms, based on SGD, are well known for being effective in using gradient information from past iterations, generating momentum or memory that enables a more accurate prediction of the true gradient slope in future iterations, thus accelerating convergence. Nevertheless, these algorithms still need an initial (scalar) learning rate (LR) as well as a LR scheduler. In this work we propose a new SGD algorithm that estimates the initial (scalar) LR via an adaptation of the ideal Cauchy step size for the multinomial logistic regression; furthermore, the LR is recursively updated up to a given number of epochs, after which a decaying LR scheduler is used. The proposed method is assessed for several well-known multiclass classification architectures and favorably compares against other well-tuned (scalar and spatially) adaptive alternatives, including the Adam algorithm.